Corporate Governance Principles in Sovereign Wealth Fund: The Case of Indonesia Sovereign Wealth Fund - Suwinto Johan (The Winners, 2022)
The research aimed to determine the application of corporate governance principles for the Indonesian Sovereign Wealth Fund (ISWF) consisting of the Supervisory Board and the Board of Directors which had different functions. The research applied a normative juridical research method. The research concludes that the government needs to review the implementation of the principles of institutional corporate governance in the ISWF. The principles of corporate governance need to be rearranged, mainly the functions and powers of the Supervisory Board and the definition of the authority of the Board of Directors. It is considered that the research has its particular limitation as the discussion is based only on two laws and one corporate governance manual. It is suggested that further research have more development by comparing corporate governance in other countries.